The Influence of The Inquiry Method on Students' Accounting Learning Outcomes in The Sub-Subject of The Balance of Class X Ak. Taman Students Medan Vocational School for The Academic Year 2021/2022 - Samio, Samio; Amin, Zulkifli (Indonesian Journal Education, 2022)
This study aims to determine whether there is an effect of learning the Inquiry method on the learning outcomes of students in class X Ak. MEDAN STUDENT TAMAN VOCATIONAL SCHOOL. The experimental class is taught by the inquiry method while the control class is taught by the conventional method.This study uses the type of instrument that is a test of students' accounting skills. Before the test is tested on students, the validity is calculated first. The validity test was also carried out by a Lecturer and one Accounting teacher. From the calculation results obtained that all tests are valid. From the test sheet validation tests by Lecturers and teachers of Accounting also stated that all tests were valid. Before testing the hypothesis, the normality test and homogeneity test were carried out using the SPSS program. Based on the results of the t-test between the average post-test values, it is obtained that the value of t count = 6.0211 at a significance level of = 0.05 and so that t count >t table . Thus, learning with the inquiry method is significantly better than learning with conventional methods. Based on the calculation of the average value of the experimental class and control class, the average value of the experimental class is higher than the control class, which is 76.84, while the average value of the control class is 74.21. By looking at the success of teaching using the inquiry method in improving student accounting learning outcomes, especially the balance sheet material